POLYMORPHISMS OF BETA CASEIN (CSN2) CDS AND INFERENCE OF ITS VARIANTS IN RIVER AND SWAMP WATER BUFFALO (BUBALUS BUBALIS) - X. Y. Fan; a; J. Xue; a; L. H. Qiu; a; R. P. Wang; Y. W. Miao (Journal of Animal and Plant Sciences, 2021)
β-casein (β-CN) has an important effect on surface properties of casein micelles and milk-clotting properties. However, current understanding of buffalo CSN2 gene polymorphisms is not sufficient. In this study, the polymorphisms in the complete coding sequence (CDS) of buffalo CSN2 were detected using PCR product direct sequencing. The CDS lengths of CSN2 gene in river and swamp buffalo were the same, which was 675 nucleotides and encoded a peptide with 224 amino acid residues. A total of 15 single nucleotide polymorphisms (SNPs) were identified in two types of buffalo. Among them, c.72C>T, c.161A>G, c.167C>T, c.168A>G, c.236G>C, c.249C>G, c.350T>C and c.391G>T were non-synonymous, which leads to the changes of p.Gly10Ser, p.Gln39Arg, p.Thr41Met, p.Gly64Ala, p.Asn68Lys, p.Met102Thr and p.Val116Phe in the mature peptide of buffalo β-CN, respectively. However, it was predicted that these substitutions had no effect on the function of buffalo β-CN. Fourteen haplotypes were defined based on the SNPs found in buffalo, and accordingly, 4 protein variants and 6 synonymous variants were added in the genetic variants of buffalo β-CN, named variant B2, B3, B4, C, C1, C2, C3, D, E and F, respectively. The main variant in river buffalo was variant B, whereas in swamp buffalo was variant C. All the variants determined in buffalo did not exist in the animals of Bos genus. In addition, there were 11 amino acid differential sites of β-CN between buffalo and Bos genus, of which Thr at residue 41 was located at the phosphorylation site. Furthermore, the results revealed that both types of buffalo β-CN were “A2-like”, which indicates that the β-CN in buffalo milk is beneficial to human health.
Keywords: Buffalo; CSN2; polymorphisms; haplotype; genetic variants